Close Reduction And Percutaneous Pinning (Crpp) Versus Open Reduction And Internal Fixation (Orif) For Fracture Of Lateral Condyle Of Humerus In Children - Akhtar, Rahman Rasool; Ashraf, Nauman; Ahmed, Riaz; Arif, Adnan; Sajid, Muhammad; Waris, Hira (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the functional outcome of CRPP with ORIF for fracture of the lateral condyle of the humerus in children. Methods: This randomised control study was conducted in the Orthopaedics Department, Rawalpindi Medical University, Rawalpindi, from 10th January 2021 to 10th July 2021. It included 60 patients aged 2 to 12 years who presented with type II lateral condyle of humerus fracture, according to Jakob’s classification. An equal number of participants, i.e., 30, were assigned to each group: the CRPP and ORIF groups. Randomisation was performed by the lottery method. The functional outcome was assessed at the 2nd month postoperatively by using modified Aggarwal criteria. Results: The patient’s age range was 2 to 12 years, and male gender was dominant in both groups. Functional outcome was excellent (93.3%) in the CRPP group as compared to the ORIF group (73.3%), good (6.7%) in the CRPP group versus 10%, fair (0%) in the CRPP group versus 10% and poor (0%) in the CRPP group versus 6.7% (p=0.116). Conclusion: CRPP could be the treatment of choice as the frequency of functional outcome of closed reduction and percutaneous pinning is statistically similar to that of ORIF. Keywords: Humeral fracture, closed reduction, Lateral condyle fracture, Displaced, open reduction